2022
DOI: 10.1371/journal.pone.0271609
|View full text |Cite
|
Sign up to set email alerts
|

How long was it for you? Memories of the duration of the UK covid-19 lockdown

Abstract: The covid-19 global pandemic has significantly impacted on the daily lives of people across the world. One consequence of this has been significant distortion to the speed at which time feels like it is passing during day-to-day life in comparison with prior to the pandemic. The current study sought to further understanding of the impact of the pandemic on temporal experience by exploring individual differences in the subjective length of the first 12 months of the pandemic in the UK. Using an online questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 51 publications
5
17
0
Order By: Relevance
“…Our results confirm previous studies that found a slow passage of time to be more prevalent than a fast passage of time 1 , 5 , 9 , and longer temporal distances to be more prevalent than shorter temporal distances 9 , 13 . Our results also show bimodality for both PoT (Passage of Time) and TD (Temporal Distance), as found in previous studies 2 , 4 , 11 , 13 . In other words, while a slow passage of time was the more prevalent direction of disruption in PoT, a notable number of participants experienced a faster passage of time.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results confirm previous studies that found a slow passage of time to be more prevalent than a fast passage of time 1 , 5 , 9 , and longer temporal distances to be more prevalent than shorter temporal distances 9 , 13 . Our results also show bimodality for both PoT (Passage of Time) and TD (Temporal Distance), as found in previous studies 2 , 4 , 11 , 13 . In other words, while a slow passage of time was the more prevalent direction of disruption in PoT, a notable number of participants experienced a faster passage of time.…”
Section: Discussionsupporting
confidence: 92%
“…A second key aspect of time judgements corresponds to subjective temporal distances 2 , 4 , 5 , 9 , 13 . Temporal distance judgements express the subject’s sense of the length of time having elapsed between a given past event and the present moment at the time of questioning (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations